The role of mechanistic target of rapamycin in maintenance of glomerular epithelial cells. Issue 1 (January 2016) - Yao, Yao; Inoki, Ken
Abstract : Purpose of review: Recent studies have emerged to reveal the pivotal roles of mechanistic target of rapamycin (mTOR) signaling not only in the maintenance of the physiological functions of renal cells but also in the pathogenesis of renal cell dysfunctions and kidney diseases. We introduce the current understanding of mTOR signaling, and its crucial roles in glomerular epithelial cell biology and the pathophysiology related to kidney diseases. Recent findings: mTOR, a Ser/Thr kinase, forms two distinct functional complexes, mTORC1 and mTORC2. Recent studies revealed that physiologic levels of mTORC1 and mTORC2 activity play key roles in maintaining podocyte and glomerular functions. However, aberrant activation of mTORC1 or loss of mTORC2 activity in podocytes may underlie the pathogenesis of glomerular disorders, including diabetic kidney disease. Summary: An effective treatment for mTORC1-associated podocyte and glomerular dysfunction may require the attenuation of mTORC1 activity in the setting of both an intact mTORC2 pathway and normal basal mTORC1 activity in order to preserve physiologic podocyte functions.